Upper Llandovery and Wenlock Cyrtograptus from the Silurian Peary Land Group, North Greenland - Bjerreskov, M (Bulletin Grønlands Geologiske Undersøgelse, 1992)
Recent collections of graptolites from the Silurian Peary Land Group in North Greenland have yielded several samples of Cyrtograptus. From this material 16 species and subspecies are described, and one new species, Cyrtograptus multibrachiatus, is erected. The described material represents a time span from the uppermost Llandovery to the uppermost Wenlock.